Nutritional Status, Physical Condition and Layer Position of The Sumedang Volleyball Athlete - Muchamad Rizki Sentani; Alam Hadi Kosasih; Lili Setiawan (Universitas Pendidikan Indonesia, 2021)
This study aims to see nutritional status, physical condition and the position of Sumedang volleyball athletes, information related to anthropometry and the physical condition of volleyball athletes based on each playing position is very useful for identifying athletes' performance when playing. In addition, for a coach this information can be used as a reference to seeing someone's faith in playing volleyball. This research method uses analysis with a descriptive approach. Data collection is done to get data related to the existing phenomenon related to the variable studied and not intended for hypothesis testing. Middle Blockers, Opposite, and Outside Hitter have more dominant playing characteristics to block opponent attacks and attacks have a higher, lower BMI, higher reach, and setter and libero have characteristics that might be more suitable for passing, receiving service opponents, and accepting the opponent's attack has shorter posture, has a heavier body, and a shorter leap coverage. There are differences in characteristics related to the needs of the position of this player related to the main task they do.